Empowerment of women and mental health promotion: a qualitative study in rural Maharashtra, India - White Joshua; Arole Rajanikant; Herrman Helen; Kermode Michelle; Premkumar Ramaswamy; Patel Vikram (BMC Public Health, 2007)
Abstract Background The global burden of mental illness is high and opportunities for promoting mental health are neglected in most parts of the world. Many people affected by mental illness live in developing countries, where treatment and care options are limited. In this context, primary health care (PHC) programs can indirectly promote mental health by addressing its determinants i.e. by enhancing social unity, minimising discrimination and generating income opportunities. The objectives of this study were to: 1. Describe concepts of mental health and beliefs about determinants of mental health and illness among women involved with a PHC project in rural Maharashtra, India; 2. Identify perceived mental health problems in this community, specifically depression, suicide and violence, their perceived causes, and existing and potential community strategies to respond to them and; 3. Investigate the impact of the PHC program on individual and community factors associated with mental health Method We undertook qualitative in-depth interviews with 32 women associated with the PHC project regarding: their concepts of mental health and its determinants; suicide, depression and violence; and the perceived impact of the PHC project on the determinants of mental health. The interviews were taped, transcribed, translated and thematically analysed. Results Mental health and illness were understood by these women to be the product of cultural and socio-economic factors. Mental health was commonly conceptualised as an absence of stress and the commonest stressors were conflict with husbands and mother-in-laws, domestic violence and poverty. Links between empowerment of women through income generation and education, reduction of discrimination based on caste and sex, and promotion of individual and community mental health were recognised. However, mental health problems such as suicide and violence were well-described by participants. Conclusion While it is essential that affordable, accessible, appropriate treatments and systems of referral and care are available for people with mental illness in developing country settings, the promotion of mental health by addressing its determinants is another potential strategy for reducing the burden of mental illness for individuals and communities in these settings.